2010
DOI: 10.1002/ange.201001061
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Tandem Cyclization of Dienol Silyl Ethers for the Preparation of Bicyclo[4.3.0]nonane Derivatives

Abstract: We previously reported the geminal carbo-functionalization reaction of alkynes on treatment of 3-siloxy-1,3-dien-7-ynes 1 with [W(CO) 6 ] or [ReCl (CO) 5 ] under photoirradiation to give bicyclo[3.3.0]octane derivatives 2 in good yield (Scheme 1). [1] The reaction was thought to proceed through nucleophilic attack of the silyl enol ether moiety to the electrophilically activated alkyne followed by attack of the generated alkenyl metallic species A to the a,b-unsaturated silyloxonium moiety at the position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Surprisingly, treatment of 11 a with [ReCl(CO) 5 ] (10 mol %) gave a 78 % yield of the tricyclic compounds 13 a and 14 a (Table 10), produced by insertion of the carbene complex moiety into the neighboring C À H bonds in the carbene complex intermediate generated by 5-exo cyclization. [25] No other cyclized products were obtained. This high insertion ability of the carbene complex intermediate is a remarkable characteristic of the rhenium(I) catalyst.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Surprisingly, treatment of 11 a with [ReCl(CO) 5 ] (10 mol %) gave a 78 % yield of the tricyclic compounds 13 a and 14 a (Table 10), produced by insertion of the carbene complex moiety into the neighboring C À H bonds in the carbene complex intermediate generated by 5-exo cyclization. [25] No other cyclized products were obtained. This high insertion ability of the carbene complex intermediate is a remarkable characteristic of the rhenium(I) catalyst.…”
Section: Introductionmentioning
confidence: 95%
“…We had already reported that on use of the cationic gold(I) catalyst, the dienol silyl ethers 11 a diastereoselectively gave the bicycloA C H T U N G T R E N N U N G [4.3.0]nonane derivatives 12 a (Scheme 10), with different stereochemistry from the thermal Diels-Alder products. [25] In these reactions, geminal carbo-functionalization through initial 5-exo cyclization gave a bicyclic carbene complex such as I, which underwent 1,2-alkyl migration of the benzylic carbon to give the product with regeneration of the catalyst. [26] During these studies, we thought of the possibility-based on previous experimental results [27] -of geminal carbo-functionalization through initial 6-endo cyclization in the presence of tungsten catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…( 3)]. [9] These ubiquitous structural scaffolds are embedded in ab road variety of naturally occurring complex alkaloids and terpenes such as magellanine (7), dankasterone (8)a nd conidiogenol (9), to name af ew.H erein, we report an efficient and stereoselective Au I -catalyzed DDAreaction that enables the preparation of angular carbocycles and its application to ashort synthesis of (AE)-magellanine (7).…”
mentioning
confidence: 99%